2002
DOI: 10.1046/j.1523-1755.2002.00362.x
|View full text |Cite
|
Sign up to set email alerts
|

Regression of left ventricular hypertrophy after conversion to nocturnal hemodialysis

Abstract: Reductions in BP with NHD are accompanied by regression of LVH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
243
1
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 336 publications
(256 citation statements)
references
References 27 publications
7
243
1
5
Order By: Relevance
“…For example, Chan et al reported an improvement in both SBP and DBP, a reduction in antihypertensive drugs and doses, and a reduction in left ventricular mass in patients undergoing nocturnal dialysis. 115 This group also reported an improvement in pharyngeal size among nocturnally dialyzed patients. 117 This may improve sleep apnea and consequently ambulatory BP.…”
Section: Frequent Dialysis and Its Effect On Bpmentioning
confidence: 84%
See 1 more Smart Citation
“…For example, Chan et al reported an improvement in both SBP and DBP, a reduction in antihypertensive drugs and doses, and a reduction in left ventricular mass in patients undergoing nocturnal dialysis. 115 This group also reported an improvement in pharyngeal size among nocturnally dialyzed patients. 117 This may improve sleep apnea and consequently ambulatory BP.…”
Section: Frequent Dialysis and Its Effect On Bpmentioning
confidence: 84%
“…115 In a cumulative analysis of 72 patients from nine centers it was noted that predialysis SBP and DBP fell within 1 month of dialysis by 13/7 mmHg from 163/94 mmHg. 116 This reduction was accompanied by a 1% decline in postdialysis weight.…”
Section: Frequent Dialysis and Its Effect On Bpmentioning
confidence: 99%
“…The study model is usually a before-and-after paradigm; frequently, a comparator group (an external control) that does not undergo the conversion to the alternative modality is added to enhance the internal validity of the study. Some relevant health parameter, such as LVM, phosphate binder use, hemoglobin concentration, or sleep pattern, is then studied while a patient is undergoing CHD and assessed again after some time interval while on NHD (19)(20)(21)(22). The presumption is that any change observed between measurements is due to the nocturnal dialysis.…”
Section: Quasi-experimental Studiesmentioning
confidence: 99%
“…Observational studies of frequent dialysis have shown salutary effects on BP (8)(9)(10)(11) and LV mass index (12)(13)(14)(15) and impressive survival rates (8,16). Moreover, LV hypertrophy has regressed in patients with ESRD who have baseline LV hypertrophy when aggressive management of BP and anemia was added to a thrice-weekly dialysis regimen (17,18).…”
mentioning
confidence: 99%
“…One such study shows that LV hypertrophy may regress without a change in relative wall thickness, another measure of LV geometry (18). In several studies, including the FHN trial, lowering BP was strongly associated with regression of LV hypertrophy (9,10,(12)(13)(14). Prior studies of frequent dialysis that evaluated LV size in addition to mass did not specifically address LV geometry (10,13).…”
mentioning
confidence: 99%